Oxidation of Petroleum Resin Based on Dicyclopentadiene Fraction - Bondaletov V. G. Vladimir Grigoryevich; Bondaletova L. I. Lyudmila Ivanovna; Nguen Van Thanh; Baikova N. Nataliya (2015, 2015)
Title screen